Suffering Silently: Alice Walker’s The Temple Of My Familiar (Journal of Namibian Studies : History Politics Culture, 2023)
The world of Alice Walker’s fiction is peopled with an amazing variety of men and women responding to the challenges of life in different ways. The present paper analyzes those characters, in Alice Walker’s The Temple of My Familiar, who appear to be living at a low level of awareness and sensitivity, stumbling through the pains and pressures of life in a rather hopeless and hapless manner. Such characters find it too difficult to face the challenges posed by the conditions of their existence and succumb to their pressures by suffering silently and submitting passively to the forces of oppression.